Adaptirovannyj kompleks gimnasticeskich upražnenij dlja povyšenija gibkosti tchekvondistov - Korneeva, A. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The article presents the results of a study aimed at theoretical justification and experimental verification of the effectiveness of a set of gymnastic exercises adapted for the training process of Taekwondo athletes focused on the development of flexibility. The research methods were: pedagogical analysis, pedagogical experiment, modeling, testing and methods of mathematical statistics. The experimental part of the study involved 24 athletes aged 21 ± 0.3 years, who were divided into two groups (EG and KG) of 12 people each. In the course of the pedagogical experiment, testing aimed at establishing the effectiveness of the proposed set of adapted gymnastic exercises was carried out at the beginning (ascertaining stage) and at the end (forming stage) of the experimental part of the study. The entire pedagogical experiment was carried out for 6 months: from August 2018 to February 2019. The results obtained in the course of the study clearly indicate the high degree of efficiency of the complex of adapted gymnastic exercises developed by us, implemented during the training process with Taekwondo athletes.